The Influence of Working Capital On The Profitability Ratio of Consumer Goods Industry Sector Companies Listed On The IDX - Andi Nila Sari; A. Ifayani Haanurat; Asri Jaya (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine and analyze the influence of working capital on the profitability ratio of companies in the consumer goods industry listed on the IDX. The type of data in this research is secondary data, namely data obtained indirectly and through intermediaries in the form of company annual report data. The type of research used in this research is quantitative with an explanatory approach. Based on the results of data research using statistical calculations through the SPSS application. The results of the research show that cash turnover and accounts receivable turnover have a positive and significant effect on profitability as evidenced by the Cash Turnover regression coefficient value (X1) of 0.068 and the calculated t value of 7.156 > 1 table 2.055 with a significant value of 0.000 < 0.05 and the coefficient value Receivables Turnover regression (X2) is 0.199 with a 1 count value of 7.1411 table 2.055 with a significant value of 0.000 0.05. Meanwhile, Inventory Turnover (X3) has a negative and significant effect on profitability as evidenced by the regression coefficient value of -0.970 and the 1 count value of -16,135 > 1 table 2.055 with a significant value of 0.000 <0.05